FAMILY THE POTENTIAL OF YOUNG MUSCOVITES AND THE PROBLEMS OF ITS IMPLEMENTATION IN A METROPOLIS - A. A. Sazonov; A. L. Sazonova (Модернизация, инновация, развитие, 2016)
The article is written on the materials of sociological survey «Youth of Moscow: value priorities and behavior strategies and prospects of development», commissioned and funded by the Department of culture of the government of Moscow in 2013, made by sociologists RSSU. The project represented a large-scale comprehensive study of an interdisciplinary nature, using a wide range of research methods, with a combination of various techniques and technologies; including: conducting large-scale survey of youth, Moscow (2000 units. OBS). Online survey (n = 300), in-depth interviews (n = 41), focus group interviews (n = 72), monitoring of social networks (220 units of observation: 20 groups in networks «Vkontakte» and «Odnoklassniki» + 200 users, the pages of which are freely available). The surveys covered the entire «old» Administrative district (excluding Moscow). The object of the study were representatives of 4 groups generation of young Muscovites aged 15 to 30 years. The article analyzes the current problems of a young family, connected with the realization of its potential. The content of the category «family potential» and its components – «the economic potential of the family», «the reproductive potential of the family», «spiritual-moral potential of the family». Examines the value attitude of young Muscovites to the family, to the love between a man and a woman; it shows the determination that their activities and behavior.